EFFECT OF DYNAMIC LOWER EXTREMITY PERFORMANCE ON KARATE ROUNDHOUSE KICK IN CHILDREN - GÖÇMEN, RECEP (FUTURE ACAD, 2018)
The main objective of this study was to determine the effect of dynamic lower extremity performance on some parameters of karate roundhouse kick (Mawashi Geri) in children. Specifically, the kinematic variables related to the displacement, reached maximal velocity of kicking leg, angle of trunk were analysed. The subject of this study composed 13 children from karate sports club. Each participant performed drop jump (0.4 m) for reactive strength parameters, the athletes were asked to demonstrate roundhouse kick performance towards the boxing mannequin using dominant legs. When the groups were evaluated according to the RSI values, it was determined that Group 2 (RSI> 1.5) recorded a longer distance by moving the kicking leg at a smaller angle, which produced less t(contact) time after the jump (p <.05). In addition, statistically significant differences were found between the V-kick values of Group 1 and Group 2 athletes and the values of Group 2 athletes were higher (p <.05). In conclusion, even though the RSI parameters have some effect on the kinematic parameters in the karate roundhouse kick performance, the study should be repeated with more study groups. (C) 2018 Published by Future Academy www.FutureAcademy.org.UK
Keywords: Reactive strength index; jump height; roundhouse kick; velocity; STRETCH-SHORTENING CYCLE; REACTIVE STRENGTH INDEX; JUMPING PERFORMANCE